Influence of stress and anxiety on students’ eating habits during the pandemic - Wüst, Marcelo; Ruttke Dillenburg Osório, Denise (O Mundo da Saúde, 2022)
The objective of this work was to analyze the influence of stress and anxiety on the eating habits of nutrition students during the COVID-19 pandemic, identifying how these mental disorders contributed to the consumption of some specific foods and associating them with the pandemic period. This is a quantitative, descriptive study, carried out during the second half of 2021, using nutrition students, of both sexes and aged over 18 years, and collection was done through Google Forms and sent via social networks (WhatsAppR). The sample consisted of 83 nutrition students, of which 96.4% (n=80) were female and 39.8% (n=33) were between 18 and 22 years old. Regarding eating habits, 75.9% (n=63) reported some change in their eating routine, 83.1% (n=69) reported a greater appetite or desire to consume high-calorie foods and 81.9% (n= 68) stated that the stress or anxiety of social isolation may have influenced their food choices. These results are perfectly understandable, given the stressful and anxiolytic environment caused by social isolation, showing that such food choices do not depend on the individual’s level of education or even course, but on a set of factors. Likewise, one cannot ignore the fact that many reported difficulties in relaxing, discouragement and sadness during the pandemic period, conditions that favor the emergence of other diseases of a psychological nature. With that, stress and anxiety were identified as possible influencers of the food choices of the evaluated students.